ANALISIS INDEKS PEMBANGUNAN MANUSIA DAN KETERSEDIAAN INFORMASI KEUANGAN TERHADAP TRANSPARANSI INFORMASI KEUANGAN DAERAH - Florensia Helma Firmanti (Bajang Institute, 2026)
This study aims to analyze the influence of the Human Development Index (HDI) on the availability of transparent regional financial information. The availability of publicly accessible financial information is a key indicator of transparency and accountability in local government. HDI, which reflects the levels of education, health, and living standards of a population, is suspected to be closely related to public demands for open access to government information. This research employs a quantitative approach using simple linear regression analysis. The data used are secondary data obtained from the Central Bureau of Statistics (BPS) and the official website of the local government of Kupang City over a certain period. The results of the study indicate that HDI has a positive and significant effect on the availability of regional financial information. In other words, the higher the HDI of a region, the more likely it is that financial information will be made publicly available. These findings highlight the importance of human development in encouraging transparent governance practices. It is hoped that this study can serve as a reference for local governments in improving the quality of public information services through strengthening education, healthcare, and social welfare.